3D sine wave‐like geometry of soft sediment deformation structures: Possible record of the Late Pleistocene seismic activity over the Teisseyre‐Tornquist Zone. (29th September 2021) - Ninard, Krzysztof; Łapcik, Piotr; Uchman, Alfred; Stachacz, Michał
Abstract: Remarkably regular load structures are recognised in the late Vistulian ( 15 ka BP) fluvial deposits exposed at the Gołąb site (eastern Poland). A mud layer, sandwiched between non‐deformed sand, exhibits the unusual morphology of a 3D sine wave with parallel crests and troughs. Such structures are reported for the first time, remarkably differing from those previously described as having perfect linearity, which could be caused by horizontal shear affecting previously liquefied sediments or by lateral migration of the sediment liquefaction front. The deformation could be triggered by either seismic shock, loading by flood waters or periglacial processes. Seismicity of the study area is evident which supports the seismogenic hypothesis.